Investigation of aluminum oxide coatings created by electrolytic plasma method in different potential regimes - Amiri, Mahsa; Padervand, Saman; Tavakoli Targhi, Vahid; Mousavi Khoei, Seyed Mohammad (Journal of Composites and Compounds, 2020)
One of the most important coating methods on aluminum surfaces is the electrolytic plasma method. The main objective of the present study is to investigate the potential of aluminum oxide coatings created by electrolytic plasma method. Aluminum series 2 and the electrolyte of sodium silicate, sodium tetraphosphate, sodium aluminate, and potassium hydroxide were used. The results showed that the appropriate voltage to achieve uniform coating with ideal thickness and morphology is 500 V. Adding sodium silicate to the electrolyte solution will create porosity and non-adhesion to the substrate. On the other hand, the use of tetra sodium pyrophosphate increases the adhesion of the coating by penetrating phosphorus into the metal/coating interface. The optimum solution for plasma electrolytic oxidation coatings composed of 10, 3, and 3 g/l of tetra sodium pyrophosphate, sodium aluminate, and KOH, respectively. DC pulsed coating was shown to control the coating process and coating uniformity. In addition, the appropriate frequency to apply coating was DC pulse potential at 1000 Hz frequency under the 30% duty cycle.